Randomised clinical trial: rabeprazole improves symptoms in patients with functional dyspepsia in Japan. Issue 7 (20th August 2013) - Iwakiri, R.; Tominaga, K.; Furuta, K.; Inamori, M.; Furuta, T.; Masuyama, H.; Kanke, K.; Nagahara, A.; Haruma, K.; Kinoshita, Y.; Higuchi, K.; Takahashi, S.; et al.
Summary Background The efficacy of proton pump inhibitors (PPIs) for treating functional dyspepsia (FD) is not well established. Aim This study, named the SAMURAI study, aimed to assess the efficacy and dose–response relationship of rabeprazole in Japanese patients with FD in a multicentre, double‐blinded, randomised, placebo‐controlled trial. Methods Investigated FD was diagnosed using the Rome III criteria. Subjects who did not respond to 1 week of single‐blind placebo treatment in a run‐in period were randomly assigned to 8 weeks of double‐blind treatment with rabeprazole 10 mg, 20 mg, 40 mg or placebo, once daily. Dyspeptic symptoms were assessed by a dyspepsia symptom questionnaire (7‐point Likert scale) and symptom diary. Results Of 392 subjects entered into the run‐in period, 338 were randomly assigned. Although there was no significant difference between placebo and rabeprazole groups in complete symptom relief for four major dyspeptic symptoms, the satisfactory symptom relief of rabeprazole 20 mg was significantly higher than placebo according to the dyspepsia symptom questionnaire (45.3% vs. 28.2%, P = 0.027) and the symptom diary assessment (48.7% vs. 30.0%, P = 0.016). The efficacy was not influenced by syndrome type or Helicobacter pylori status. No statistically significant differences in the incidence of adverse events were seen among treatment groups. Conclusions Rabeprazole 20 mg once daily but not 10 or 40 mg significantly provides satisfactory symptom relief for functional dyspepsia (ClinicalTrials.gov, Number NCT01089543).